The innovation journal the public sector innovation journal. (The Innovation Journal], 1995)
A non-partisan Internet-based journal devoted to sharing ideas and information about public sector innovation. Public servants, elected officials, academics, consultants and others share their thoughts through TIJ. The Innovation Journal's mission is to encourage innovation which will improve the quality, efficiency or effectiveness of government administration and policy.